Ovide veut parler ». Les négociations de Clément Marot traducteur - Claivaz, David (Cahiers d'Humanisme et Renaissance, 2016)
This is the first French verse version of Ovid's Metamorphosis, translated by the sixteenth century poet Clément Marot. Marot's translation marks not only a literary achievement, but also cleaves to deontological standards worthy of modern translators. A systematic analysis of the text reveals Marot's choices of variation, as well as their deep coherence.